Nuclear field theory and the inelastic scattering of structureless particles by nuclei - Dussel, G. G.; Maqueda, E. E.; Perazzo, R. P. J. (American Physical Society, 1978)
Fil: Dussel, G. G. Comisión Nacional de Energía Atómica; Argentina